Aksara Jawi dalam Naskah Sarana Walio - Inayatusshalihah Inayatusshalihah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2017)
Abstract Buton was a maritim sultanate in Southeast Sulawesi. It had a strategic location because it was a centre of transit and trade in Nusantara and Asia. This situation caused cultural contact and arose new Butonese culture. A kind of cultural product is literate tradition using such as Jawi script (Arabic-Malay) that appeared from interaction of local culture, the Butonese, with islam. In history of Buton many kitab was writen in Jawi script including Kitab Sarana Walio. Taking descriptive-qualitative method, the writer analyze Jawi script that was used in Sarana Walio text. This analyze was related with cultural context that underlied the appearance of this script. This research has found the system of writing with Jawi script in this manuscript. Based on ortographic system, Jawi script in Sarana Walio is not different from ortography of Arabic-Malay system in Nusantara. Graphem consist of consonant and vocal which is symbolized by huruf saksi, not punctuation. Meanwhile, there’s inconsistence in the case of word writing in manuscript. —Abstrak Buton merupakan kesultanan maritim di Sulawesi Tenggara yang memiliki letak strategis karena menjadi pusat persinggahan dan perdagangan Nusantara dan Asia. Hal ini tentu saja menyebabkan terjadinya kontak budaya yang memunculkan bentuk-bentuk kebudayaan baru di masyarakat Buton. Salah satunya adalah tradisi tulis aksara Jawi (Arab-Melayu) yang lahir dari interaksi budaya lokal masyarakat Buton dengan Islam. Banyak kitab dalam sejarah Buton yang ditulis dalam aksara Jawi, di antaranya Kitab Sarana Walio. Dengan menggunakan metode deskriptif-kualitatif, penulis mengkaji aksara Jawi dalam teks Sarana Walio, dihubungkan dengan konteks budaya yang melatari munculnya aksara tersebut. Penelitian telah menemukan adanya sistem penulisan aksara Jawi dalam naskah tersebut. Ditinjau dari ortografinya, aksara Jawi dalam Sarana Walio tidak berbeda dengan sistem ejaan Arab-Melayu pada umumnya di Nusantara. Grafem terdiri atas grafem konsonan dan grafem vokal yang dilambangkan dengan huruf saksi, tidak dengan tanda baca. Selain itu, ada inkonsistensi penyalin naskah dalam penulisan beberapa kata.DOI: 10.15408/al-turas.v23i1.4794